Food insecurity among consumers from rural areas in Romania - Paştiu, Carmen Adina; Maican, Silvia Ştefania; Dobra, Iulian Bogdan; Muntean, Andreea Cipriana; Haţegan, Camelia (Frontiers in Nutrition, 2024)
Food security has a special relevance in nowadays economies, due to the current crisis, characterized by multiple layers on a social, political, economic and individual biological level. The present study aims to identify relevant aspects of food insecurity for consumers in rural Romania and the main factors that significantly influence it (food availability, food access, food consumption). The data were collected from a sample of 875 consumers from rural areas in Romania. The results show that food insecurity is perceived by the consumers of Romanian rural households as being strongly influenced by food availability, but less influenced by food consumption and access. The results have an essential relevance in the development of agri-food marketing strategies and public policies in the field of sustainable development.